Penggunaan Pengeras Suara dalam Berdoa (Zikir) Perspektif Quran Surah Al-A’raf: 205 Studi Analisis Tafsir Al-Azhar Karya Buya Hamka - Fitriyana, Fitriyana; Damanik, Agusman; Ismahani, Siti (TSAQOFAH, 2023)
Humans basically often ask or plead to other than Allah Swt. In order to fulfill their desires instantly and this phenomenon is known as polytheism. Islam has a way to avoid it, namely by dhikr. Remembrance is an activity or speech that aims to remember the Creator, namely Allah Swt, with the intention of getting closer to Him, usually by mentioning Asmaul Husna (names of Allah). Dhikr can be done anytime and anywhere except places where it is prohibited, the dhikr order is made with the aim of obeying Him, as a reminder of the afterlife, sincere and confident in the help of Allah Swt. The data used is a literature study that is used in ways to pursue various information about the procedures for remembrance in Islam through books or the internet that are appropriate to the cases discussed. solving the problem of how to do dhikr in Islam, namely l) zikir zhohir, 2) dhikr khofi. In conclusion, remembrance can be done verbally (dhikr zhohir), heart (dhikr khofi) and is a commendable action where we remember through praises to Allah Swt. The results of this study indicate that it is permissible to recite the dhikr out loud using a loudspeaker or low voice with the provisions that have been explained by the Koran itself and the opinion of the clergy in order to avoid unwanted things. This research is included in the library research category and the data analysis technique used in this research is descriptive comparative analysis technique. The main sources of data are the Koran, the book of Tafsir Al-Azhar, coupled with related literature such as journals, theses, books or related articles. The purpose of this research is to find out how Buya Hamka interprets QS. Al-A'raf 205.